Pengujian Aplikasi Doctor to Doctor Menggunakan Metode Black Box Testing - Findra Kartika Sari Dewi; Stephanie Pamela Adithama; Albert Teonando Suhardi (KONSTELASI: Konvergensi Teknologi dan Sistem Informasi, 2023)
The existence of smartphones has an impact on mobile application development which aims to help humans in their daily activities. The Doctor to Doctor (D2D) application is an application that helps doctors get the latest information about health. To maintain the quality of the application so that it is comfortable to use by users, it is necessary to carry out tests with the aim of finding errors in the application. D2D application testing is done manually and automatically based on functional tests. This test uses an automated testing application, namely Katalon Studio. Tests were carried out on 16 of the 42 functions in the D2D application. In this study, we will compare the level of effectiveness of manual and automated testing as well as the advantages and disadvantages of manual and automated testing. Based on the results of the tests that have been carried out, the percentage of successful D2D application testing was 86.89% indicating that 7 of the 16 functions were still not running properly. From the results obtained in terms of time, automated testing using Katalon Studio is not effective enough compared to manual testing.